Euskal Gramatika prozesatzen: hastapenetako zenbait emaitza - Laka, Itziar; Zawiszewski, Adam; Erdozia, Kepa (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
After a brief introduction to ERP methods in the study of language, we report some recent results from a set of experiments investigating morphosyntactic processing in Basque. First we report results from experiments that focus on word-order processing, with special attention to verb medial sentences, where subjects show no preference for either SVO or OVS orders, in contrast with the sharp asymmetry found in SOV versus OSV orders in previous work. Second, we report results from a set of conductual and ERP experiments targeted to explore object agreement, which suggest that it is neurocognitively distinct from subject agreement.